This realm of New Zealand the sovereign, the Governor-General, the Crown - Quentin-Baxter, Alison; McLean, Janet 1963- (Auckland University Press, 2017)
"New Zealand is a democratic constitutional monarchy, one of Queen Elizabeth II's sixteen realms. This book provides a comprehensive account of how the Queen, the Governor-General and the Crown interact with our democratically-elected leaders under New Zealand's unwritten constitution. The authors explain how these islands in the South Pacific were first brought within Queen Victoria's dominions, the arrangements then made for their future government, and how those arrangements developed over time with the pressure for democracy and responsible government to become New Zealand's current constitution. They discuss the responsibilities of, and interactions between, the key office-holders: the Sovereign herself; her representative, the Governor-General; the impersonal and perpetual Crown, and the Prime Minister, other Ministers and Members of Parliament. All of them affect in some way the government which runs the country day to day. In an afterword, the authors examine some of the key issues to be considered should New Zealand become a republic"...Publisher's website